2023
DOI: 10.1038/s12276-022-00907-9
|View full text |Cite
|
Sign up to set email alerts
|

TPX2 prompts mitotic survival via the induction of BCL2L1 through YAP1 protein stabilization in human embryonic stem cells

Abstract: Genetic alterations have been reported for decades in most human embryonic stem cells (hESCs). Survival advantage, a typical trait acquired during long-term in vitro culture, results from the induction of BCL2L1 upon frequent copy number variation (CNV) at locus 20q11.21 and is one of the strongest candidates associated with genetic alterations that occur via escape from mitotic stress. However, the underlying mechanisms for BCL2L1 induction remain unknown. Furthermore, abnormal mitosis and the survival advant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 44 publications
4
11
0
Order By: Relevance
“…Since we also observed that the stress kinase JNK is activated upon TPX2 expression and dasatinib addition leads to a significant reduction of JNK activation (Figure 2), we deeply analyzed the impact of TPX2 expression on YAP signaling, demonstrating that TPX2 high levels promote YAP activation and this is probably the reason for dasatinib-increased sensitivity (Figure 3). Our data is concomitant with previous works showing that TPX2 expression increases YAP signaling in breast cancer cells, and this is dependent on Aurora A kinase activity [81,82,97]. Moreover, Aurora A is also known for modulating SRC through the cofactor NEDD9, affecting dasatinib response [108].…”
Section: -Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Since we also observed that the stress kinase JNK is activated upon TPX2 expression and dasatinib addition leads to a significant reduction of JNK activation (Figure 2), we deeply analyzed the impact of TPX2 expression on YAP signaling, demonstrating that TPX2 high levels promote YAP activation and this is probably the reason for dasatinib-increased sensitivity (Figure 3). Our data is concomitant with previous works showing that TPX2 expression increases YAP signaling in breast cancer cells, and this is dependent on Aurora A kinase activity [81,82,97]. Moreover, Aurora A is also known for modulating SRC through the cofactor NEDD9, affecting dasatinib response [108].…”
Section: -Discussionsupporting
confidence: 91%
“…TPX2 expression leads to a reduction in the YAP inhibitory phosphorylation at Ser127, elevated levels of TAZ, and increased pSer909-LATS1 (Figure 3B), which is in accordance with the described YAP-LATS1 feedback loop [80], and with previous data showing that TPX2 also leads to YAP/TAZ stabilization and activation [81,82]. This YAP activation is reversed when dasatinib is added to TPX2-expressing cells, restoring YAP-Ser127 phosphorylation and recovering basal levels of TAZ protein (Figure 3B).…”
Section: 2-src Kinase Signaling Pathway Evaluation Upon Tpx2 Inductionsupporting
confidence: 92%
“…S5F). These findings suggest that the TEAD family of TFs, consistent with YAP activation (or the loss of Hippo signaling) in culture-adapted variants (Kim et al, 2023;Price et al, 2021;Weissbein et al, 2019), may be pivotal in achieving culture-adapted phenotypes.…”
Section: Epigenetic Alteration Effects On Genetic Alteration Regardin...mentioning
confidence: 93%
“…However, the 20q11.21 gain alone is insufficient to drive precise phenotypic changes such as 'acquired survival advantage (Jo et al, 2020).' Thus, additional cue would be necessary to induce BCL2L1 and TPX2 gene transcription, which yields clear 'acquired survival traits' through BCL-xL protein and YAP/TEAD4-dependent gene expressions, respectively (Avery et al, 2013;Cho et al, 2018;Kim et al, 2023;Nguyen et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation